Approaches to implement safe by design in early product design through combining risk assessment and Life Cycle Assessment. (January 2023) - Subramanian, Vrishali; Peijnenburg, Willie J.G.M.; Vijver, Martina G.; Blanco, Carlos F.; Cucurachi, Stefano; Guinée, Jeroen B.
Abstract: The Safe by Design (SbD) concept aims to ensure the production, use and disposal of materials and products safely. While there is a growing interest in the potential of SbD to support policy commitments, such as the EU Green Deal and the Circular Economy Action Plan in Europe, methodological approaches and practical guidelines on SbD are, however, largely missing. The combined use of Life Cycle Assessment (LCA) and Risk Assessment (RA) is considered suitable to operationalize SbD over the whole life-cycle of a product. Here, we explore the potential of the combined use of LCA and RA at Technological Readiness Level (TRL) 1–6. We perform a review of the literature presenting and/or developing approaches that combine LCA and RA at early stages of product design. We identify that basic early-on-evaluations of safety (e.g., apply lifecycle thinking to assess risk hotspots, avoid use of hazardous chemicals, minimize other environmental impacts from chemicals) are more common, while more complex assessments (e.g., ex-ante LCA, control banding, predictive (eco)toxicology) require specialized expertise. The application of these simplified approaches and guidelines aims to avoid some obvious sources of risks and impacts at early stages. Critical gaps need to be addressed for wider application of SbD, including more studies in the product design context, developing tools and databases containing collated information on risk, greater collaboration between RA/LCA researchers and companies, and policy discussion on the expansion from SbD to Safe and Sustainable by Design (SSbD). Graphical abstract: Application of Risk Assessment and Life Cycle Assessment along TRL Image 1 Highlights: The combined use of Life Cycle Thinking (LCT) or Life Cycle Assessment (LCA) and Risk Assessment (RA) is considered suitable to operationalize Safe by Design (SbD)for product design. Our review of combined use of LCT/LCA and RA at Technological Readiness Levels (TRL) 1–6 found that product design teams can already perform themselves basic early-on-evaluations of safety and sustainability while collaborating with experts or value chain actors for more complex assessments (ex-ante LCA, control banding, predictive toxicology, etc). Studies in product design context, development of tools and databases from the product designer's perspective, collaboration between RA/LCA researchers and companies, and expansion from SbD to Safe and Sustainable by Design (SSbD) is needed for better implementation of SbD.